2001
DOI: 10.1128/jb.183.18.5317-5324.2001
|View full text |Cite
|
Sign up to set email alerts
|

l -Threonine Export: Use of Peptides To Identify a New Translocator from Corynebacterium glutamicum

Abstract: Bacterial mechanisms for the uptake of peptides and their hydrolysis to amino acids are known in great detail, whereas much less is known about the fates of the peptide-derived amino acids. We show that the addition of L-threonine-containing di-or tripeptides results in reduction of the growth of Corynebacterium glutamicum, with concomitant high intracellular accumulation of L-threonine to up to 130 mM. Using transposon mutagenesis and isolation of mutants with increased Thr peptide sensitivity, nine open read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 53 publications
(45 reference statements)
1
108
0
Order By: Relevance
“…To get access to such reactions, we used DNA microarrays to probe for altered mRNA levels as a further approach to identify L-serine-degrading reactions (26). To enable a high intracellular L-serine concentration, we added the tripeptide Ser-Ser-Ser, which is hydrolyzed upon uptake and thus ensures a high intracellular L-serine concentration (51). Total RNA was isolated 70 min after peptide feeding, and relative RNA levels were determined by hybridization to DNA microarrays representing 95.5% of the open reading frames of C. glutamicum (NCBI NC003450).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To get access to such reactions, we used DNA microarrays to probe for altered mRNA levels as a further approach to identify L-serine-degrading reactions (26). To enable a high intracellular L-serine concentration, we added the tripeptide Ser-Ser-Ser, which is hydrolyzed upon uptake and thus ensures a high intracellular L-serine concentration (51). Total RNA was isolated 70 min after peptide feeding, and relative RNA levels were determined by hybridization to DNA microarrays representing 95.5% of the open reading frames of C. glutamicum (NCBI NC003450).…”
Section: Resultsmentioning
confidence: 99%
“…After 4 h of growth, from an OD 600 of 0.8 to an OD 600 of 3.5, 1 mM seryl-tripeptide was added to one of the cultures and the cells were further incubated to reach an OD 600 of 7 before harvest. Intracellular quantification of the amino acid pools (51) confirmed that addition of 1 mM seryl-tripeptide to the exponentially growing culture resulted in an intracellular L-serine concentration of 95 mM, whereas the concentration in the control culture without peptide was 1 mM. The harvesting of 25-ml aliquots of the cultures and the entire procedure of RNA preparation, cDNA synthesis, DNA microarray hybridization, washing, data normalization, and gene expression analysis have been described previously (18,26).…”
Section: Methodsmentioning
confidence: 99%
“…2a). One of the ORFs upstream of otsA (NCgl2533) encodes a transmembrane threonine exporter (Simic et al, 2001). An oppositely oriented ORF downstream of otsB is predicted to encode a LacI-familytype transcription regulator which might be involved in the regulation of the otsA and otsB genes.…”
Section: Analysis Of C Glutamicum Genome Sequence Datamentioning
confidence: 99%
“…Based on these pioneering studies, Eggeling and coworkers successfully identified novel transporter families responsible for amino acid efflux. [11][12][13][14] Although it has been suggested that the secretion of L-glutamate by C. glutamicum is mediated by a carrier system in the cytoplasmic membrane, 15,16) the nature of the L-glutamate exporter has long been unclear (for reviews, see references 7-9, 17). We found recently that the NCgl1221 gene, which encodes a mechanosensitive channel homolog, is involved in the mechanism of L-glutamate secretion.…”
mentioning
confidence: 99%